In Vitro Polyploidy Induction of Patchouli (Pogostemon Cablin Benth.) by Colchicine - Afifah, Ulil Azmi Nurlaili; Wiendi, Ni Made Armini; Maharijaya, Awang (Journal of Tropical Crop Science, 2020)
Patchouli (Pogostemon cablin Benth.; 2n = 32) is an aromatic herbaceous plant commonly cultivated for use in the the fragrance industry. As patchouli is propagated by cuttings polyploidization induction by colchicine treatment was conducted to obtain a new genotype with high patchouli alcohol content. This research aimed to increase patchouli genetic diversity with colchicine treatment by the formation of a polyploid plant. Axillary buds from single node cutting of aseptic plantlets were used as the explants. The experiment was arranged using a factorial completely randomized design with two factors, namely the concentration of colchicine and the immersion duration. Genetic diversity of patchouli was successfully enhanced by adjusting the colchicine concentration and immersion treatment. lethal concentration (LC) of 50% in patchouli was 0.132% and the LC 50% for soaking time was 60.16 hours. The number of chloroplasts, stomatal length and chromosome number increased with increasing ploidy, whereas stomatal density and the number of trichomes decreased. The chromosome number of 16 patchouli mutants in generation 4 was still unstable, and a chimera was found with mixoploidy between 20-80. A hierarchical dendogram clustered 16 patchouli mutants into four different groups.